FAKTOR-FAKTOR YANG MEMPENGARUHI LOYALITAS PENGGUNA APLIKASI RUANGGURU DI KOTA JAMBI - Asrin Amer, Ayu Rizki Anggraini (JUSS (Jurnal Sains dan Sistem Informasi), 2022)
This study aims to see the factors that affect the loyalty of users of the Ruangguru application in Jambi City. This research was conducted by using purposive sampling method, namely the sampling technique by determining the criteria specified in the sampling. The number of respondents who were determined as samples in this study were 100 high school students in Jambi City who had used the Ruangguru application. The analysis technique used to interpret and analyze the data in this study is the Structural Equation Model (SEM) technique using Partial Least Square (PLS) software to see the influence between variables in the research model. The final result of this research is that it is known that the aesthetic quality factors, namely typography, color and content quality, have a significant effect on user trust in the Ruangguru application, organizational structure and layout factors, namely interactivity which have a significant effect on user trust in the Ruangguru application, but navigation has no significant effect on user trust. Meanwhile, the trust factor as well as the switching cost have a significant effect on the loyalty of the Ruangguru application.